Distribution of refugees very uneven among EU member states - even when accounting for economic strength and total population - Karl Brenke (DIW Economic Bulletin, 2015)
The European Union is currently experiencing its largest influx of asylum seekers in years. Yet the distribution of these refugees across the member states is highly uneven: Large countries such as the United Kingdom, France, Italy, and Spain, as well as the Eastern European countries (apart from Hungary), have received relatively few asylum seekers. Far more refugees are headed to Central Europe, Sweden, and the small countries on the outskirts of the EU (Malta, Cyprus, and Bulgaria). Germany is likewise receiving an above-average number of asylum seekers: Assuming a uniform distribution across all EU countries, Germany receives three times as many in relation to its total population, and twice as many in relation to its economic strength. And now, as some of the member states are beginning to enact more restrictive refugee policies, this geographic concentration of asylum seekers is expected to increase even more. There is therefore an urgent need for the EU Member States to agree on a more uniform - and thus more fair - distribution of the refugees. In Germany, 37 percent of asylum seekers were granted protection status upon completing the asylum procedure in the first seven months of 2015. According to available data, however, the integration of these refugees into the German labor market has presented numerous difficulties. The number of unemployed individuals - which was initially low - has increased among the members of the most frequently represented refugee nationalities. Among all Syrians living in Germany with a residence permit, for example, there are more unemployed individuals than there are social security- paying employed individuals. The ratio is only slightly better for people from Iraq, Afghanistan, Somalia, and Eritrea. Accordingly, the proportion of Hartz IV benefits recipients among these groups is high. It is assumed that these problems are significantly mitigated the longer the recognized refugees remain in Germany and the greater command they have over the German language. The study of German should therefore be better supported.
Keywords: F22; J10; 330; asylum seekers; European Union; Germany; labour market integration